The Influence of Profitability and Liquidity Ratios on Financial Performance - Manao, Uci Defi Arfila; Dewi, Idah Kusuma (Indonesian Journal of Islamic Economics and Finance, 2025)
The financial performance of PT. Sumber Bintang Rejeki fluctuated in the period from 2020 to 2024. Therefore, the purpose of this study is to assess the company's financial performance with the presence of fluctuations. The quantitative data used in this study are secondary data taken from financial reports. The data analysis method uses profitability and liquidity ratios to calculate and assess financial performance. The findings of the study show that the greater the profitability ratio, the better the company's financial performance. The liquidity ratio has a significant influence on the financial performance of PT Sumber Bintang Rejeki, that the company manages current asset liquidity well so that it has more optimal financial performance. Both ratios, namely profitability and liquidity, simultaneously have a significant impact on the financial performance of PT Sumber Bintang Rejeki. In conclusion, despite fluctuations, profitability and liquidity have a positive impact on financial performance separately and simultaneously on the company's financial performance.